Knowledge Regarding Childhood Anemia among Mothers of Under Five Children in a Maternal and Child Health Clinic of a Tertiary Hospital - Pokharel, Sunita; Adhikari, Jamuna (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Anemia is the commonest nutritional problem in the world, mostly in developing countries. In Nepal, more than half of children aged six to 59 months are anemic. Anemia causes a lot of morbidity and mortality in children under five years. Thus, objective of this study is to find out the level of knowledge regarding childhood anemia among mothers of under five children. Methods: This is a cross sectional descriptive study among mothers having children under five years of age selected by using non-probability purposive sampling method. Structured questionnaire in Nepali version were used to interview with mothers in a Maternal and Child Health Clinic of Tribhuvan University Teaching Hospital, Kathmandu, Nepal. The study was conducted for 12 weeks. Results were analyzed by using descriptive (frequency, percentage, mean, standard deviation, median, interquartile range) and inferential statistics (Chi Square test) in SPSS version 20. Results: Total 206 mothers participated in the study. Nearly two third (62.1%) had high level of knowledge regarding childhood anemia among mothers of under-five children. There is statistical association between level of knowledge and occupation of mothers (p < 0.05). Conclusions: The level of knowledge is high in nearly two third of mothers of under five children regarding childhood anemia. Therefore, health education program should be launched by management committee to increase the knowledge of the mothers.